(untitled) (CIPEEX, 2024)
The “Socorro!” app aims to help the user when he needs it most, when it is necessary to use emergency numbers to solve problems. The focus on security applied to the user, who will use the application in cases of need through external force, was widely discussed, since there are similar solutions on the market, but none specifically counts with all the emergency numbers existing at the national level, based on in this, an application model was prototyped, capable of responding to this need, where the interface will be summarized in a button and the information referring to the user will be previously filled and at the time of use, sent to the competent authority. On the creation of this application, we sought to analyze the existing models of solutions for user safety, as well as the response time of the authorities or those responsible for solving the problem in question, starting from the user’s call for assistance. One of the main points raised was the focus on the user experience, since the application must be used in emergency situations, it must be simple and minimalist, but effective and reliable. Some methodologies were used to map users, as well as to define the application’s user interface. Methods such as Design Thinking, Color Theory and Creation of personas became essential for the success of the creation of MVPS, which will be used for testing and validation of the project. The application uses as a premise the Doherty’s Threshold Laws, which concerns the speed within the product and establishes an international standard of 0.4 seconds of application response, and the Hick-Hymann’s Law, which is responsible for the need for ease in the interface of an application. With the combination of these laws, it is possible to guarantee that the application will be fast, minimalist and easy to understand for the user.